Transparency of Political Parties in Spain and e-Accesibility for People with Disabilities - Sánchez Medero, Gema; Pastor Albaladejo, Gema; Jiménez Meroño, Sergio (Revista del CLAD Reforma y Democracia, 2022)
This article analyses the transparency webs of Spanish political parties in order to verify whether they are accessible to people with disabilities (hearing, visual, motor or cognitive) and also to establish which elements determine or condition, to a greater or lesser extent, the level of accessibility of these spaces. To this end, an evaluation model was generated (4 criteria, 10 variables and 31 indicators) inspired by the guidelines for the development of e-accessibility of the Web Content Accessibility Guidelines (WCAG) 2.1 of the World Wide Web Consortium (W3C), which was applied through the use of automatic and manual techniques for the web pages’ review. In addition, the Pearson Correlation Coefficient was used to determine the relationship between the degree of incidence or relationship of a series of factors (active transparency index, seniority, number of votes and number of deputies) on the level of accessibility of the transparency portals of the political parties. The research provides novel results, which will allow us to verify whether political parties manage inclusive transparency. That is, whether the websites, generated to comply with their legal obligations in terms of active advertising, favour the access of all people to e-information, including people with disabilities so that they can exercise their political citizenship on an equal footing with the rest.
Keywords: Transparency; Access to Information; Political Party; Disability; Disabled Persons; Citizenship; Spain